Nosocomial Infection in Patients with Severe and Critical COVID-19 - M. V. Bychinin; I. O. Antonov; T. V. Klypa; I. A. Mandel; A. I. Minets; N. A. Kolyshkina; Ya. B. Golobokova (Общая реаниматология)
The aim of the study was to determine the etiology and frequency of nosocomial infections in patients with severe and critical COVID-19.Material and methods. A retrospective, single-center study included 168 patients with COVID-19 admitted to the intensive care unit (ICU). All episodes of infection, clinical and laboratory characteristics, and outcome were documented in patients.Results. Hospital-acquired infections were detected in 82 (48.8%) of 168 patients, more frequently in men (p = 0.028).  A total of 232 episodes of nosocomial infections were observed including ventilator-associated pneumonia (48.2%), bloodstream infection (39.2%), nosocomial pneumonia/tracheobronchitis (13.4%), and urinary tract infection (5.2%). The main causative agents of nosocomial infections were resistant strains of Acinetobacter baumannii and Klebsiella pneumoniae. Infections developed on the average on day 6 [3; 9] of ICU stay and were associated with the initial severity of the patients assessed by SOFA (p=0.016), SpO2 (p=0.005), lymphopenia severity (p=0.003), Neutrophil-Lymphocyte Ratio (p=0.004), C-reactive protein (p=0.01), aspartate aminotransferase (AST) level (p=0.022), or vitamin D (p=0.035) levels. Patients diagnosed with infection were more likely than those without infections to require mechanical ventilation (67.6% vs 32.4%, p < 0.001), high-flow oxygen therapy (50.0% vs 31.0%, p = 0.020), renal replacement therapy (36.8% vs 9.3%, p = 0.003), and had longer ICU length of stay (13 [9; 18] vs 4 [2; 8], p < 0.001), hospital length of stay (19 [14; 29] vs 15 [11; 20], p = 0.001) and mortality (47 (57.3%) vs 25 (29.0%), p < 0.001).Conclusion. In patients with severe and critical COVID-19 a high incidence of nosocomial infections was found, which negatively affected the outcome. In more than half of the cases, the infection was caused by resistant strains of Gram-negative bacilli. Procalcitonin is a useful biomarker for identifying bacterial infection in patients with COVID-19.